World Energy Markets and OPEC Stability - Ezzati, Ali. (Lexington, Massachusetts: Lexington Books- D.C. Heath & Company, 1978)
This book presents an analytical framework for evaluating policy issues concerning world energy markets. The framework is designed to closely approximate the behavior of all important aspects of those markets.
Includes index.
Bibliography: p. 185-198.
ne 18/04/2018
Loan
Keywords: Energy Policy; Petroleum Industry and Trade